Implikasi Teori Belajar Humanisme terhadap Pembelajaran Bahasa Arab / Implications of Humanistic Learning Theory on Arabic Language Learning - Isop Syafei (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
This research aims to explore the theory of humanism in Arabic language learning, its implications for the design, implementation, and evaluation of Arabic language learning, as well as the strengths and limitations of humanism theory in Arabic language learning. The research method employed a literature review to analyze the implications of humanism theory in Arabic language learning. The steps involved identifying sources, reading and analyzing them, synthesizing information, and developing a conceptual framework. The findings of the research indicate that: (1) Applying humanism theory in Arabic language learning promotes inclusivity, intrinsic motivation, personal growth, and strong teacher-student relationships. (2) Teacher-student interaction in humanism-based Arabic language learning strengthens relationships, creates an inclusive and supportive environment, and encourages student participation. (3) Implementing humanism-based Arabic language learning involves supportive and inclusive teacher-student interactions that foster trust. (4) Humanism-based evaluation in Arabic language learning focuses on personal growth, positive feedback, student involvement, meaningfulness, and increased motivation. (5) The strengths of humanism theory include student empowerment, personal growth, meaningful experiences, and inclusive environments. Its limitations include a lack of structure, limited emphasis on cognitive abilities, assessment challenges, and suitability for all students.Abstrak: Penelitian ini bertujuan untuk mengetahui teori humanisme dalam pembelajaran bahasa Arab, implikasinya terhadap disain pembelajaran bahasa Arab, implikasinya terhadap implementasi pembelajaran bahasa Arab, implikasinya terhadap evaluasi pembelajaran bahasa Arab, serta kelebihan dan kekurangan teori humanisme dalam pembelajaran bahasa Arab. Metode penelitian ini menggunakan studi literatur untuk menganalisis implikasi teori humanisme terhadap pembelajaran bahasa Arab. Langkah-langkah meliputi identifikasi sumber, pembacaan dan analisis, sintesis informasi, dan pembangunan kerangka konseptual. Hasil penelitiannya menunjukkan bahwa: (1) Penerapan Teori Humanisme dalam pembelajaran bahasa Arab mendorong inklusivitas, motivasi intrinsik, pertumbuhan pribadi, dan hubungan yang kuat antara guru dan siswa. (2) Interaksi guru-siswa dalam pembelajaran bahasa Arab berbasis teori humanisme memperkuat hubungan, menciptakan lingkungan inklusif dan mendukung, serta mendorong partisipasi siswa. (3) Implementasi pembelajaran bahasa Arab berbasis teori humanisme melibatkan interaksi guru-siswa yang saling mendukung, inklusif, dan memperkuat kepercayaan. (4) Evaluasi bahasa Arab teori humanisme: pertumbuhan pribadi, umpan balik positif, melibatkan siswa, bermakna, motivasi meningkat. (5) Kelebihan Teori Humanisme: pemberdayaan siswa, pertumbuhan pribadi, pengalaman bermakna, lingkungan inklusif. Kekurangannya: kurangnya struktur, kurangnya penekanan pada kemampuan kognitif, tantangan penilaian, ketidakcocokan dengan semua siswa.